The role of Primary Care in the context of the COVID-19 pandemic in Brazil (Research, Society and Development, 2021)
This study carried out an integrative literature review on the role of primary health care in Brazil in the context of the Covid-19 pandemic. Data collection was performed in the databases: LILACS, SCIELO and CAPES portal. The descriptors used were: “Primary Health Care”, “Family Health Strategy”, “Covid-19” associated with each other by the Boolean operator AND. Articles related to the topic of the study, available in full, in Portuguese and published from january 2020 to march 2021, were included. Protocols or technical documents, theses, dissertations and monographs were excluded. The articles included in the sample were read in full for identification, description and analysis of the topics covered. It was observed that coping strategies against Covid-19 in primary health care in Brazil permeated two aspects: the reorganization of the work process and the actions and activities developed, emphasizing health education for producing knowledge and providing opportunities for self-care. The results of this study highlighted the potential of primary health care in confronting Covid-19, highlighting the importance of strengthening it, especially in this period of pandemic.